Standard Time Measurement Of Erection & Dismantling Of Tubular Scaffold Vs Modular Scaffold To Design Work Method - Charoonsri Rizani, Nataya; Erika, Erika; Agung, Bambang (International Journal of Advanced Multidisciplinary, 2023)
The large demand for the use of scaffolding is a problem for contractors, especially for profitability and work productivity. If the selection of the type of scaffolding is not in accordance with expectations both in terms of working time and wage costs for scaffolding workers, as well as safety factors which are also important in the selection of the type of scaffolding will cause cost overruns. One of the efforts made is to replace conventional methods to be more scientific, namely measuring the standard time in the installation and dismantling of scaffolding, so that the standard work time is obtained as a reference for the work method used. Measurements were made of two types of installation and dismantling, namely tubular scaffolding and modular scaffolding. Setting standard time using performance rating and allowances that were adjusted to workplace conditions.Based on the measurements, it was found that the standard time for installation and dismantling of tubular type scaffolding they were 2 hours 7 minutes and 39 minutes respectively, while for modular scaffolding they were 25 minutes and 8 minutes respectively.